Halogen bonds, chalcogen bonds, pnictogen bonds, tetrel bonds and other sigma-hole interactions: a snapshot of current progress - Brammer Lee; Peuronen Anssi; Roseveare Thomas M (Wiley-Blackwell Publishing, Inc., 2025)
We report here on the status of research on halogen bonds and other sigma-hole interactions involving p-block elements in Lewis acidic roles, such as chalcogen bonds, pnictogen bonds and tetrel bonds. A brief overview of the available literature in this area is provided via a survey of the many review articles that address this field. Our focus has been to collect together most review articles published since 2013 to provide an easy entry into the extensive literature in this area. A snapshot of current research in the area is provided by an introduction to the virtual special issue compiled in this journal, comprising 11 articles and entitled 'Halogen, chalcogen, pnictogen and tetrel bonds: structural chemistry and beyond.'